Pemberdayaan Dayah Melalui Pelatihan Penyusunan Laporan Keuangan - Trie Nadilla; Almira Keumala Ulfah; Husni Kamal; Muhammad Syafril Nasution; Ramadhan Razali (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
The Daarul Ikhlaash Al-Aziziyyah Islamic Education Institute (Dayah) located in Banda Sakti District, Lhokseumawe City is an institution that is active in the religious field and is managed independently. A common problem faced by dayah today is the absence of a system of recording, preparation and reporting of finances, as well as operational management and governance which is also still not good. In connection with the problems in the dayah, the orientation of this service program is to provide education and training to dayah administrators to be able to compile their financial statements independently and responsibly. So that the ability to make decisions from dayah income/expenditure becomes wiser. The solution offered by the community service implementer is training in preparing financial statements with simple bookkeeping techniques. The application of science and technology referred to in this activity is to assist dayah administrators in managing dayah finances easily. With the purpose and purpose of providing training in the preparation of this report, it can help dayah management in managing finances professionally.